Feminizing the Fetish : Psychoanalysis and Narrative Obsession in Turn-of-the Century France - Apter, Emily S., 1954- (Book collections on Project MUSE., 1991)
Emily Apter offers a fresh account of the complex relationship between representation and sexual obsession in turn-of-the-century French culture, and in particular the theme of ""female fetishism"" in the context of the feminine culture of mourning, collecting, and dressing